Evaluation of British and Canadian Conductive Rubber Heating Elements for Handwear: Preliminary Report - Nolan, Richard W; Cattroll, Stanley W (1978)
A physiological evaluation of British and Canadian conductive rubber heating elements for use in electrically-heated handwear was carried out in the DREO cold room at -40 C. It was found that the difference between the mean hand temperatures of test subjects wearing either type of handwear was not significant. (Author) Abstract in French.